Repressing HIF-1α-induced HDAC9 contributes to the synergistic effect of venetoclax and MENIN inhibitor in KMT2Ar AML - Qing Ling; Yutong Zhou; Yu Qian; Jiejing Qian; Yi Zhang; Jinghan Wang; Yanan Zhu; Yile Zhou; Juying Wei; Chunmei Yang; Jie Sun; Wenjuan Yu; et al. (BMC, 2023)
Abstract KMT2A-rearranged acute myeloid leukemia (KMT2Ar-AML) is an aggressive subtype of AML with poor response and prognosis. KMT2Ar-AML has been demonstrated to be sensitive to BCL2 inhibitor venetoclax (VEN), but these patients are unable to benefit from current VEN-based regimen (VEN plus azacitidine or low dose-cytarabine), so a novel and KMT2A rearrangement-specific targeting partner is required, and MENIN inhibitor (MEN1i) is a promising one. Herein, we investigated the effect and mechanism of VEN plus MEN1i in KMT2Ar-AML. Our results showed that VEN and MEN1i exhibited a striking synergistic effect in KMT2Ar-AML cell lines (in vitro), primary KMT2Ar-AML cells (ex vivo), and MOLM13 xenotransplantation model (in vivo). Furthermore, we found that VEN plus MEN1i significantly enhanced apoptotic induction in KMT2Ar-AML cell lines. VEN or MEN1i monotherapy disrupted balance of BCL-2/BCL-XL or down-regulated HOXA9/MEIS1, respectively, but these mechanisms were not further strengthened by their combination. RNA-Sequencing identified that HDAC9 was specifically repressed by VEN plus MEN1i rather than monotherapy. We demonstrated that HDAC9 was indispensable for KMT2Ar-AML proliferation and its repression contributed to proliferation inhibition of VEN plus MEN1i. Moreover, we found that hypoxia induced HDAC9 expression in KMT2Ar-AML, and VEN plus MEN1i inhibited hypoxia pathway, especially HIF-1A, and its target HDAC9. As our results indicated, VEN plus MEN1i-mediated HDAC9 down-regulation was partially dependent on HIF-1A repression in KMT2Ar-AML. Hypoxia induction sensitized KMT2Ar-AML to VEN plus MI-503-mediated proliferation inhibition and apoptosis induction. Therefore, repressing HIF-1A-induced HDAC9 contributed to the synergistic effect of VEN and MEN1i in KMT2Ar-AML.